Răspunsuri

2014-06-02T20:17:27+03:00
 Aplici formula : \frac{x-x1}{x2-x1} = \frac{y-y1}{y2-y1}

AB: \frac{x-3}{5-3}= \frac{y-5}{7-5}
(inmultin cu 2 casa dispara numitorul ) => x-3+y-5=> AB: x-y+2=0=>y=x+2=>panta e 1

BC: \frac{x-5}{-1-5} =  \frac{y-7}{2-7} => -5x+25=-6-42 =>BC:-5x-6y+67= 0=>tex] y=\frac{-5}{6}x + \frac{67}{6} [/tex] panta e -5/6

[tex]AC: \frac{x-3}{-1-3}= \frac{y-5}{2-5} => -3x+9=-4y+20=>AC:-3x+4y-11=0 [/text]=>4y=3x+11=>y=3/4x+11/4 =>panta e 3/4


stiam si eu asta il vroiam rezolvat
gata, l-am rezolvat